2008
DOI: 10.1105/tpc.108.058339
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisProtein Disulfide Isomerase-5 Inhibits Cysteine Proteases during Trafficking to Vacuoles before Programmed Cell Death of the Endothelium in Developing Seeds

Abstract: Protein disulfide isomerase (PDI) oxidizes, reduces, and isomerizes disulfide bonds, modulates redox responses, and chaperones proteins. The Arabidopsis thaliana genome contains 12 PDI genes, but little is known about their subcellular locations and functions. We demonstrate that PDI5 is expressed in endothelial cells about to undergo programmed cell death (PCD) in developing seeds. PDI5 interacts with three different Cys proteases in yeast two-hybrid screens. One of these traffics together with PDI5 from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 97 publications
(111 reference statements)
2
82
0
Order By: Relevance
“…However, little is known about their functions and their subcellular locations in Arabidopsis seeds. It has been reported that PDI5 (At1g21750) chaperones and inhibits cysteine proteases during trafficking to vacuoles prior to programmed cell death of the endothelium in developing seeds (86), and this protein is oxidized during Arabidopsis seed germination (50). In rice seeds, a PDI protein (LOC_Os11g09280) prevents proglutelin and prolamin from aggregating by chaperoning their segregation in the ER lumen (87,88).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about their functions and their subcellular locations in Arabidopsis seeds. It has been reported that PDI5 (At1g21750) chaperones and inhibits cysteine proteases during trafficking to vacuoles prior to programmed cell death of the endothelium in developing seeds (86), and this protein is oxidized during Arabidopsis seed germination (50). In rice seeds, a PDI protein (LOC_Os11g09280) prevents proglutelin and prolamin from aggregating by chaperoning their segregation in the ER lumen (87,88).…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis genome contains 12 PDI genes (86). PDIs are thiodisulfide oxidoreductases that catalyze disulfide bond formation and rearrangements in the substrate proteins, facilitating the folding of nascent polypeptides in the endoplasmic reticulum (ER).…”
Section: Discussionmentioning
confidence: 99%
“…In the soybean (Glycine max) cotyledon, P5 subfamily oxidoreductase PDIM associates noncovalently with proglycinin, 11S globulin-type storage protein (Wadahama et al, 2008). In Arabidopsis, PDI5 (PDIL1;1) regulates the timing of programmed cell death in endothelial cells (Andè me Ondzighi et al, 2008), and PDIL2;1 plays a role in embryo sac development (Wang et al, 2008). In Arabidopsis liquid culture, the PDI family oxidoreductases respond differently to various types of stresses (Lu and Christopher, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chaperoning and inhibition of cysteine proteases by protein disulfide isomerase-5 during trafficking to vacuole before PCD [56] Vacuole (PSV and Lytic Vacuole)…”
Section: Er-derived Compartments Accumulation and Release Of Cysteinementioning
confidence: 99%